2013
DOI: 10.1038/nature12038
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 regulates TNF-α secretion through hydrolysis of long-chain fatty acyl lysine

Abstract: The Sir2 family of enzymes or sirtuins are known as nicotinamide adenine dinucleotide (NAD)-dependent deacetylases1 and have been implicated in the regulation of transcription, genome stability, metabolism, and lifespan2, 3. However, four of the seven mammalian sirtuins have very weak deacetylase activity in vitro. Here we show that human Sirt6 efficiently removes long chain fatty acyl groups, such as myristoyl, from lysine residues. The crystal structure of Sirt6 reveals a large hydrophobic pocket that can ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
794
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 636 publications
(813 citation statements)
references
References 28 publications
18
794
0
1
Order By: Relevance
“…First, the activity of SIRT6 was assessed using an excess of peptide (5 mM (Fig. 1B), respectively, consistent with a prior study (13). In addition, SIRT6 was able to deacylate the decanoyl (96%) and dodecanoyl (98%) groups from lysine residues.…”
Section: Long-chain Deacylase Activity Is An Intrinsic Activity Of Mostsupporting
confidence: 65%
See 4 more Smart Citations
“…First, the activity of SIRT6 was assessed using an excess of peptide (5 mM (Fig. 1B), respectively, consistent with a prior study (13). In addition, SIRT6 was able to deacylate the decanoyl (96%) and dodecanoyl (98%) groups from lysine residues.…”
Section: Long-chain Deacylase Activity Is An Intrinsic Activity Of Mostsupporting
confidence: 65%
“…Consistent with this idea, Jiang et al (13) demonstrated recently that SIRT6 preferentially hydrolyzes long-chain fatty acyl groups, including myristoyl and palmitoyl groups, from lysine residues. A crystal structure of SIRT6 bound to a myristoylated peptide supported this observation.…”
mentioning
confidence: 69%
See 3 more Smart Citations